(untitled) (PJDOL, 2023)
This study highlighted the willingness of knowledge sharing practices of university teachers. It also identified the intervening role of work culture and organizational commitment on the willingness of knowledge sharing of faculty. It was a quantitative study with survey research design. The sample of the study was selected through simple random sampling technique. Data were collected from 1130 faculty members of 13 public sector universities of Punjab. Tools of the study were two in numbers, i.e., open ended questionnaire and a five-point Likert scale. Data were collected about three variables: knowledge sharing, work culture and organizational commitment. Collected data were analyzed and presented in the form of different tables, graphs and charts. It was concluded from the analysis of data that university faculty involve themselves in knowledge sharing practices and their willingness for knowledge sharing was affected by work culture and organizational commitment.